1970
DOI: 10.1002/pssa.19700010411
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the antiferromagnetic transition of CrN

Abstract: The preparation of nitrides of chromium has been studied in detail. Oxygen free samples of Cr1.000Nx, x ranging from 0.997 to 0.980, have been prepared by equilibrating at temperatures from 850 to 1048 °C in one atmosphere pressure of nitrogen. Results of the temperature dependences of expansivity, lattice parameters, magnetic susceptibility and electrical resistivity of CrN of various compositions are reported. The antiferromagnetic → paramagnetic transformation in CrN exhibits temperature hysteresis and is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
94
3
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 3 publications
19
94
3
4
Order By: Relevance
“…The data clearly shows a 0.14% increase of lattice constant at 270-284 K, indicating a phase transition for the polycrystalline CrN layer. The 0.14% increase is within previously reported values of 0.08% 7 and 0.24%, 11 where the relatively large difference between these studies is likely due to impurities, particularly for bulk samples, and substrate induced stress for the thin film studies.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The data clearly shows a 0.14% increase of lattice constant at 270-284 K, indicating a phase transition for the polycrystalline CrN layer. The 0.14% increase is within previously reported values of 0.08% 7 and 0.24%, 11 where the relatively large difference between these studies is likely due to impurities, particularly for bulk samples, and substrate induced stress for the thin film studies.…”
supporting
confidence: 87%
“…3,4 Electronic transport studies report controversial results for CrN, including (i) values for the resistivity ρ at room temperature range over more than two orders of magnitudes, from 1.7×10 -3 to 3.5×10 -1 Ωcm, 3,[5][6][7][8][9][10] even when only considering the most reliable data for single crystal CrN layers; (ii) the temperature dependence of ρ shows metallic behavior with dρ/dT > 0 in some studies, 6,7,11 but an increase in ρ with decreasing temperature in other reports, 3,5,9,12 which has been attributed to the presence of a band gap 5 or carrier localization due to crystalline defects 13 or N-vacancies; 14 (iii) some studies report a discontinuity in ρ(T) at 260-280 K, 3,6,7,14 which is associated with a magnetic and structural phase transition from a paramagnetic NaCl structure at room temperature to a low-temperature antiferromagnetic orthorhombic P nma phase 11,15 with a 0.56-0.59% higher density, 11 and a 25% lower bulk modulus, 16 while other reports show no evidence for a phase transition in the ρ(T)-curves. 5,7,9 Electronic structure calculations suggest that magnetic stress relief couples magnetic ordering with the structural phase transition, 17 and that CrN exhibits a band gap if the Hubbard Coulomb interaction term is sufficiently large.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Considerable experimental and theoretical work have demonstrated that CrN undergoes a magnetic and structural phase transition from a paramagnetic NaCl structure at room temperature to a low-temperature antiferromagnetic orthorhombic P nma phase at N eel temperature of 273-286 K. [5][6][7] A variety of electrical transport properties in CrN have been observed, such as, a semiconducting behavior with dq/dT < 0, [8][9][10][11] a metallic behavior with dq/dT > 0, [12][13][14] and continuous and discontinuous q(T) curves at 260-280 K. [8][9][10][11][12][13]15 These differences in electrical transport properties have been attributed to the sensitivity of the transport properties to N stoichiometry. 12,15 In addition, the discontinuity in q(T) curves has usually been observed in CrN powders or polycrystalline CrN films, rather than in epitaxial films, suggesting that the epitaxial constraints could affect the transition. 14,16 Therefore, it is necessary to carry out a comparative study of the electrical transport properties of polycrystalline and epitaxial CrN films with different N concentrations in order to clarify the conductance mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…26 Even if this kind of small cluster existed, one would expect to observe superparamagnetism, instead of the ferromagnetism as we show here. In addition, CrN or Cr 2 N clusters, if present, would not contribute to the observed ferromagnetism, because CrN is antiferromagnetic and Cr 2 N is not ferromagnetic between 85 and 500 K. 27 Thus, the presence of Cr clusters cannot be the source of the enhanced ferromagnetism in AlCrN films grown at low nitrogen pressures.…”
mentioning
confidence: 99%